Can macrocyclic phosphonate molecules inhibit barium sulfate crystallization? - Radomirovic, T.; Ogden, Mark; Rohl, Andrew; Jones, Franca (The Royal Society of Chemistry, 2019)
Macrocyclic compounds such as DOTP (1,4,7,10-tetraazacyclododecanetetrakis(methylenephosphonic acid)) and NOTP (1,4,7,-triazacyclononanetri(methylenephosphonic acid)) are found to inhibit precipitation of barium sulfate just as potently as their non-cyclic counterparts depending on the ionisation state of the molecule. Morphologically, DOTP has a more significant influence on the shape of barium sulfate particles formed than NOTP while turbidity results show that NOTP does not significantly affect the induction time observed, unlike DOTP, which does impact the induction time at higher concentrations. Overall, the inhibition of these macrocyclic compounds can be explained by the number of de-protonated phosphonate groups and is not significantly impacted by the presence of the ring. The presence of calcium ions during barium sulfate crystallization lowers the degree of inhibition for both NOTP and DOTP. Molecular modelling showed that an uncomplexed DOTP molecule could lattice match to the barium sulfate lattice but had fewer Ba?Ophos interactions than the equivalent non-macrocyclic molecule. The comparison of uncomplexed with complexed DOTP shows that the final configuration is similar for these two situations, thus in this case it is not the Ba?Ophos interactions but the overall replacement energy that is important.